Cover Feature: Highly Active N, O Zinc Guanidine Catalysts for the Ring‐Opening Polymerization of Lactide (ChemSusChem 18/2017). Issue 18 (18th September 2017) - Schäfer, Pascal M.; Fuchs, Martin; Ohligschläger, Andreas; Rittinghaus, Ruth; McKeown, Paul; Akin, Enver; Schmidt, Maximilian; Hoffmann, Alexander; Liauw, Marcel A.; Jones, Matthew D.; Herres‐Pawlis, Sonja
Abstract : The Back Cover picture shows our new zinc carboxyguanidine catalyst for the ring‐opening polymerization of lactide to polylactide (PLA), a biodegradable polyester. Lactide originates from maize, sugar beets, or sugar cane as renewable resources. PLA is well‐known but up to now industrially produced only by tin catalysts. Our catalyst represents a viable alternative for the melt polymerization (monitored by Raman spectroscopy) owing to its extraordinary robustness and activity. More details can be found in the Full Paper by Schäfer et al. (onpage 3547 in Issue 18, 2017 DOI:10.1002/cssc.201701237 ).